1997
DOI: 10.1093/clinids/24.1.57
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Ampicillin/Sulbactam Versus Imipenem/Cilastatin in the Treatment of Limb-Threatening Foot Infections in Diabetic Patients

Abstract: A cost-effectiveness analysis was performed following a double-blind, randomized study of ampicillin/sulbactam (A/S) versus imipenem/cilastatin (I/C) for the treatment of limb-threatening foot infections in 90 diabetic patients. There were no significant differences between the treatments in terms of clinical success rate, adverse-event frequency, duration of study antibiotic treatment, or length of hospitalization. Costs of the study antibiotics, treatment of failures and adverse events, and hospitalization w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 18 publications
2
34
0
Order By: Relevance
“…4,5 Studies that evaluated other serious infections in the hospital attribute less than 10% of overall health care costs to antimicrobials. [6][7][8][9] A recent study analyzed costs associated with managing hospitalized patients with CAP (PSI [Pneumonia Severity Index] Class IV and V) at a community health system during a 6-month period. 10 The median total hospital cost per patient was $5,078, while the antimicrobial acquisition cost accounted for $139 per patient (2.7% of the total cost).…”
Section: Antimicrobial Costs As a Proportion Of Total Health Care Costmentioning
confidence: 99%
“…4,5 Studies that evaluated other serious infections in the hospital attribute less than 10% of overall health care costs to antimicrobials. [6][7][8][9] A recent study analyzed costs associated with managing hospitalized patients with CAP (PSI [Pneumonia Severity Index] Class IV and V) at a community health system during a 6-month period. 10 The median total hospital cost per patient was $5,078, while the antimicrobial acquisition cost accounted for $139 per patient (2.7% of the total cost).…”
Section: Antimicrobial Costs As a Proportion Of Total Health Care Costmentioning
confidence: 99%
“…vancomycin, teicoplanin of therapy is an important factor in selecting a regimen, antibiotics account for only a small portion of the treatment costs for a foot infection [46]. Comparative trials and economic analyses of various anti-infective regimens are needed [47]. Empirical antibiotic recommendations, by type of infection, are given in Table 3.…”
Section: S72 Benjamin a Lipskymentioning
confidence: 99%
“…Variables that explained 95% of the total treatment costs were the time intervals between diagnosis, the final required procedure, and wound healing and the number of surgical procedures performed [69]. One American study demonstrated that therapy with ampicillin/sulbactam was significantly less expensive than therapy with imipenem/cilastatin, for limb-threatening diabetic foot infections, primarily because of the lower drug and hospitalization costs and the less severe side effects associated with the former treatment [70]. More comparative trials and economic analyses are needed.…”
Section: Antibiotic Therapymentioning
confidence: 99%